2011
DOI: 10.1073/pnas.1105195108
|View full text |Cite
|
Sign up to set email alerts
|

Drinking a hot blood meal elicits a protective heat shock response in mosquitoes

Abstract: The mosquito's body temperature increases dramatically when it takes a blood meal from a warm-blooded, vertebrate host. By using the yellow fever mosquito, Aedes aegypti, we demonstrate that this boost in temperature following a blood meal prompts the synthesis of heat shock protein 70 (Hsp70). This response, elicited by the temperature of the blood meal, is most robust in the mosquito's midgut. When RNA interference is used to suppress expression of hsp70, protein digestion of the blood meal is impaired, lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
116
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(126 citation statements)
references
References 31 publications
1
116
0
1
Order By: Relevance
“…An increased accumulation of heat shock protein 70 (HSP70) was detected as early as 1 hPBM and its presence is attributed to protection from the stress of warm blood ingestion (Benoit et al 2011). HSPs are encoded by a gene family that has expanded in the Ae.…”
Section: Resultsmentioning
confidence: 99%
“…An increased accumulation of heat shock protein 70 (HSP70) was detected as early as 1 hPBM and its presence is attributed to protection from the stress of warm blood ingestion (Benoit et al 2011). HSPs are encoded by a gene family that has expanded in the Ae.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the increased mortality induced by the ingestion of CXM appears to be due to the ingestion of a warm blood meal, as CXM-fed mosquitoes that were not blood-fed had mortality rates similar to those of sucrose-fed (control) mosquitoes (16% of mortality). These results suggest that the drug might also impair their ability to deal with the heat stress generated by the ingestion of warm blood (Benoit et al, 2011).…”
Section: Memory Characterisationmentioning
confidence: 89%
“…There is some indication that adult anopheline mosquitoes can avoid the warmest locations [45], but there is little evidence for precise behavioural thermoregulation [46]. Additionally, it has been shown that expression of mosquito heat-shock proteins increase in response to thermal stress [47] and these proteins have been shown to interact with Plasmodium development [48]. The extent to which these interactions would affect EIP in these environments is unclear, but should be considered in future studies.…”
Section: Discussionmentioning
confidence: 99%